The Human–Nature Experience: A Phenomenological-Psychoanalytic Perspective - Schweitzer, Robert D.; Glab, Harriet; Brymer, Eric (Frontiers in Psychology, 2018)
Drawing upon phenomenology and psychoanalytic concepts, we explore and explicate participants’ lived experience of the natural world. The authors draw upon Husserl’s description of consciousness as intentionality and his later work on the life-world, in exploring experiences which provide a basis for a psychochoanalytic understanding of the human-nature experience. Unstructured interviews were undertaken with nine participants, each of whom regarded nature as being significant for their sense of wellbeing. The lived experiences were explicated drawing upon the two processes: Giorgi’s descriptive phenomenological psychological methodology and psychoanalytic researcher reflexivity. Data analysis and explication involved the following steps: (1) a thorough reading of each interview transcript, (2) breaking data into parts by demarcating meaning units, (3) organizing data by translating meaning units into units of psychological experience through coding, and (4) arriving at a summary of the data which involved organizing and reviewing units of psychological experience. The process of reflection led to the formulation of an essential psychological structure of participants’ lived experience of the natural world. We argue that the human-nature relationship can be conceived in terms of psychoanalytic concepts, and in particular, constructs based upon an understanding of the primacy of attachment relationships. The natural world is elucidated as (a) nature being experienced as a primary attachment, (b) nature experienced as a secure base, (c) nature experienced as twinship, (d) nature experienced as containing, and (e) nature experienced as embodied. This paper extends previous empirical descriptions of the human-nature relationship by incorporating psychoanalytic processes and theory into a theoretically informed qualitative methodological stance. Beyond the traditional notion of nature as something ‘out there’ that we can interact with for cognitive or emotional restoration, participants in this study described the experience of nature as being integral to their sense of self. This study suggests that experiences that facilitate immersion in nature provide opportunities for the development of an integrated sense of self that has a profound impact on a participant’s sense of wellbeing. The findings further demonstrate the convergence between phenomenology and psychoanalytic constructs which offers a richness to our understanding the subjectivity of participants and their relationship with nature,